Drinking water quality analysis after 22 deaths in LaeMaromas, North Sumatera - Abraham Simatupang; Seruni Kusuma Udyaningsih Freisleben; Maruli Pandjaitan; Christel Westerhausen; Hans Joachim Freisleben (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2014)
The case of 22 deaths in LaeMaromas, North Sumatera suspected due to water contamination bynearby metal mining was brought by local citizens to the Church-supported non-governmentalorganization (NGO) Persekutuan Diakonia Pelangi Kasih (PDPK). The patients’ clinical symptomswere fever, shivering, shaking chills, abdominal pain, diarrhoea, and vomiting. In June 2011, ateam from the District Health Department analysed the drinking water quality, especiallymicrobiological contamination. Members of PDPK asked the German-Indonesian MedicalAssociation to conduct a second complete water analysis with focus on heavy metal content.Six water samples from four different wells in LaeMaromas and two from Sopokomil and Bongkaraswere analysed according to international water quality standards. Taste, odour, colour, and turbiditywere determined by organoleptic and photometric methods. Temperature and pH were measuredwith a calibrated thermometer and pH-meter. Total dissolved solids were determined gravimetrically,hardness as CaCO3 content. Inorganic anions and nitrogen compounds were measured by titration.Contamination with Eschericia coli and coliform bacteria, organic compounds and detergents wasdetermined according to standard methods. Heavy metals were measured by atomic absorptionspectroscopy. The pH of the water (4.5-6.5) was below standard (6.5-8.5). Heavy metals werewithin the allowed concentrations. All samples from LaeMaromas contained high counts coliformbacteria /E. coli with a peak of 1600 counts/100 mL and high organic compound level of 63 mg/Lin LaeMaromas III. Most probably, the 22 deaths were caused by drinking water contamination withcoliform bacteria rather than by heavy metals or other chemicals.